Static and Dynamic Analysis of the Shielded Tunnel in Alluvium Soil with 2D FEM Model - Khan, M.A. (Springer, 2021)
Transportation tunnels are strategic parts of all urban development projects. Challenges are faced while selecting the excavation techniques and support types in these underground constructions. Hence, sufficient information and knowledge are required while designing the shield support system in soft ground tunnelling. In this study, a two-dimensional plane strain finite element simulation of a tunnel having 350-mm thick reinforced concrete liner has been carried out. The effects of soil stratification, degree of saturation, and seismic loading have been considered for the analyses. Mohr-Coulombâs constitutive model has been adopted to simulate the linear elastic-plastic behaviour of soil in static analysis. Furthermore, the dynamic response of horizontal shear waves (S-wave) has also been investigated on the tunnelâs model. It was observed numerically that the stresses and deformation reduced to 15 and 30 respectively when sandy silt (SM), soil layer moved towards liner in stratification analysis. The tangential and radial stresses increased by 24 and 35, respectively, due to groundwater presence above the crown. Moreover, vertical and horizontal settlements have increased exponentially that led to a reduction in the shear strength of soil due to variation in water level. Also, ovaling (egging) deformation was observed in the liner due to the propagation of seismic shear waves at the base of the tunnel. Â© 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.